Analysis of the Employee Commitment and Supply Chain Integration Effects on Industrial Enterprise - Ivanovna Kulikova, Lidiya; Bagramovna Sungatullina, Liliya; Ilshatovna Sabirova, Aigul (International Journal of Supply Chain Management, 2020)
Abstract— To study methodological approaches to employee remuneration planning taking into account the relationship between the types of supply chain management (SCM) and the staff effectiveness based on the multiple regression model and evaluation of the optimal payment times based on a dynamic model with a distributed lag. The application of the concept of sustainable supply chain management in the operation strategy of industrial enterprise seems to be a very important function. This supply chain also covers all three aspects of sustainable development: business, environmental, and social. The linear multiple regression model, classical least squares method, dynamic model with a distributed lag. The article considers a methodological approach to planning staff remuneration taking into account the supply chain management requirements. The relationship between the types of wages and the employees’ labor productivity is revealed and the optimal payment times are established to devise the best remuneration plan in supply chain process to each employee. The article develops a methodological approach to remuneration planning based on the relationship between supply chain and employee effectiveness based on the dominant types of remuneration and optimal payment times. The developed methodological approach to planning staff remuneration was disclosed based on the data of a shoe enterprise from 2016 to 2020. Meanwhile, managers should promote employee commitment not only for better supply chain success, but also to mitigate the barriers of supply chain management implementation. The main conclusions of the article can be used in the scientific and practical activities of manufacturing enterprises when planning supply chain strategies by evolving the employees.